2003
DOI: 10.1093/toxsci/kfg111
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tissue Repair in Survival from S-(1,2-Dichlorovinyl)-L-Cysteine-Induced Acute Renal Tubular Necrosis in the Mouse

Abstract: S-(1,2-Dichlorovinyl)-L-cysteine (DCVC), a model nephrotoxicant in mice, causes acute tubular necrosis and death at high doses. Our earlier studies revealed that renal tissue repair was critical for survival in mice with DCVC nephrotoxicity. The objective of this study was to investigate if increasing renal tissue repair could protect mice from the lethal outcome of DCVC. Male Swiss Webster (SW) mice were administered a low dose of DCVC (15 mg/kg, ip) 72 h before injection of a normally lethal dose of DCVC (75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
34
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 38 publications
7
34
0
Order By: Relevance
“…doses in all the groups. Comparing the findings in the present experiment with those at 1 week after acute exposure (Vaidya et al, 2003a), BUN values at 1 mg/kg p.o. and i.p.and 10 mg/kg p.o.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…doses in all the groups. Comparing the findings in the present experiment with those at 1 week after acute exposure (Vaidya et al, 2003a), BUN values at 1 mg/kg p.o. and i.p.and 10 mg/kg p.o.…”
Section: Discussionsupporting
confidence: 68%
“…However, very few subchronic and chronic studies have been implemented for toxicity expression by chronic exposure of DCVC. Thus, in the present study, exposure was determined to be performed once a week according to Vaidya et al (2003a) suggesting that time around 120 hr was required to recover from the renal dysfunction (blood urea nitrogen (BUN), urine excretion volume, glucosuria) caused by DCVC at 15 mg/kg, and the period of the experiment was determined to be 13 weeks, same as a previous subchronic exposure study on TCE (NTP, 1990). In addition, examination was conducted at 1 week after the last administration, assuming renal function to have been showing indications of recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Calabrese and Mehendale (1996) reviewed the role of altered tissue repair as an adaptive strategy to chemical exposures. Of more direct pertinence to the present study, Mehendale and colleagues (Korrapati et al, 2005(Korrapati et al, ,2006Vaidya et al, 2003aVaidya et al, ,2003bVaidya et al, ,2003c) demonstrated in a series of studies in mice that enhanced renal cell division is associated with protection of mice from DCVC-induced acute renal failure and death. Their studies have described what they have termed "auto-protection."…”
Section: Discussionsupporting
confidence: 56%
“…One possibility is that prior exposure to Hg 2+ may induce one or more forms of renal cysteine conjugate β-lyase, as has been shown for the mercapturate of hexachlorobutadiene (Cooper and Pinto, 2006;MacFarlane et al, 1993). Similarly, understanding of the mechanism by which pretreatment of hPT cells with TRI or DCVC decreases toxicity of Hg 2+ also requires further study, but may involve activation of certain transcription factors and/or some of the protective mechanisms, such as activation of cellular repair and proliferation, as described by Mehendale and colleagues (Korrapati et al, 2005(Korrapati et al, ,2006Vaidya et al, 2003aVaidya et al, ,2003bVaidya et al, ,2003c. Some of our earlier results in primary cultures of hPT cells, studying the effects of DCVC on expression of regulatory proteins such as heat shock protein 27 (Hsp27), p53, and nuclear factor κB (NFκB) (Lash et al, 2005), are consistent with such a potential mechanism.…”
Section: Discussionmentioning
confidence: 89%
“…Proximal tubular injury initiated by low to moderate doses of DCVC is repaired by timely and adequate stimulation of cell division and renal tissue repair, restoration of renal structure and function, and survival of mice by averting ARF-bound injury. 1 Nephro-autoprotection is characterized by prior administration of a low dose of DCVC, which primes renal cell division such that tissue repair is no longer inhibited even after exposure to a normally lethal dose of DCVC (28,64,65). The critical role of cellular signaling mechanisms in stimulating renal cell division and sustaining renal tissue repair in the autoprotection model has been documented (27,28,66).…”
mentioning
confidence: 99%